An urban overhead? Crime, agglomeration, and amenity - Stuart Donovan; Thomas de Graaff; Henri L.F. de Groot; Aaron Schiff (Tinbergen Institute, 2023)
Using data for 134 locations in New Zealand, we study the effects of crime and agglomeration on urban amenity. We find that crime has significant negative effects on the value of urban amenity, with elasticities of approximately ?0.06 for firms and ?0.09 for workers. To put this effect in context, this implies the value of urban amenity for workers is approximately 2–3 times more sensitive to crime than average temperature. More uniquely, we find that controlling for crime leads to somewhat larger estimates of agglomeration economies. Together, these results suggest that crime detracts significantly from the value of urban amenity and may also act as an urban congestion cost that serves to undermine agglomeration economies.
Keywords: R21; R31; C11; 330; crime; urban development; agglomeration economies; amenity; New Zealand